Pier Luigi Pizzi - Tornare a sognare il già sognato: il ’Furioso’ televisivo di Luca Ronconi ed Edoardo Sanguineti - Volpe, Andrea (Firenze Architettura, 2018)
Ronconi and Sanguineti’s «Orlando Furioso» is considered one of the most innovative productions in Italian experimental theatre. Thanks to Pier Luigi Pizzi, the TV version repeats the success of the prototype not only by reinterpreting in an exemplary way the work of Vignola but also by demonstrating in its intimate nature as an architectural text how it is possible to wonderfully combine avant-garde and tradition.